Sickle cell disease in Saudi Arabs in early childhood. Issue 3 (March 1981) - Perrine, R P; John, P; Pembrey, M; Perrine, S
Abstract : Haemoglobin electrophoresis screening of 2341 infants from the oases of eastern Saudi Arabia, performed in an attempt to detect cases early and then to follow up and give better management to patients with sickle cell disease, showed 20% with S-trait and 43 with sickle cell disease (37 HbSS and 6 S-beta(0) thalassaemia). On follow-up from birth (or from 3 months) for a mean of 3 1/2 years there was more morbidity and mortality than in matched Saudi Arab controls, but these rates were lower than for affected black infants in the US or Jamaica. Serial haemoglobin levels were l g/dl lower than for controls; height and weight increases were the same. Mean fetal haemoglobin level was 32% at 4-5 years. Half of a subsample of 23 cases had evidence of coexistent alpha-thalassaemia which appeared to protect against functional asplenia, judged by the presence of Howell-Jolly bodies; however there was no difference in degree of anaemia or clinical course. Early screening is recommended for infants at risk for sickle cell disease, and comprehensive care should be given even if the infant has the less severe type.